2013
DOI: 10.1093/annonc/mdt140
|View full text |Cite|
|
Sign up to set email alerts
|

Phase III trial of concurrent thoracic radiotherapy with either first- or third-cycle chemotherapy for limited-disease small-cell lung cancer

Abstract: In LD-SCLC treatment, TRT starting in the third cycle of chemotherapy seemed to be noninferior to early TRT, and had a more favorable profile with regard to neutropenic fever.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 16 publications
2
69
1
3
Order By: Relevance
“…When platinumbased chemotherapy is used concurrently with TRT, 2-and 5-year survival rates have been shown to favour of early TRT. Also in Sun et al (2013) phase III trial 222 LS-SCLC patients were evaluated, and they showed that, TRT starting in the third cycle of chemotherapy had noninferiority to early TRT. Response rates, OS, and PFS were comparerable in both arms (Sun et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When platinumbased chemotherapy is used concurrently with TRT, 2-and 5-year survival rates have been shown to favour of early TRT. Also in Sun et al (2013) phase III trial 222 LS-SCLC patients were evaluated, and they showed that, TRT starting in the third cycle of chemotherapy had noninferiority to early TRT. Response rates, OS, and PFS were comparerable in both arms (Sun et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Also in Sun et al (2013) phase III trial 222 LS-SCLC patients were evaluated, and they showed that, TRT starting in the third cycle of chemotherapy had noninferiority to early TRT. Response rates, OS, and PFS were comparerable in both arms (Sun et al, 2013). Results of different studies on early vs late TRT were shown at (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Life expectancy was shortened by .10 years among the current smokers compared with those who had never smoked. Adults who had quit smoking [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] or 45-54 years of age gained approximately 10, 9 and 6 years of life, respectively, compared with those who continued to smoke. This is in complete agreement with the UK observation.…”
mentioning
confidence: 99%
“…Despite controversial findings in the literature [67][68][69], most data and guidelines support early thoracic radiotherapy beginning with the first or second cycle when cisplatin-based chemotherapy is used [26,39,68,[70][71][72], as the majority of studies indicate a benefit with early radiotherapy [73].…”
Section: Radiochemotherapymentioning
confidence: 99%